How Reliable and Valid Is the Student Autonomy Scale When Examined Through the Rasch Model? - Yuca, Verlanda; Suherman, Uman; Nurihsan, Juntika; Budiman, Nandang; Magistarina, Elrisfa (International Journal of Research in Counseling and Education, 2025)
Autonomy can influence students to regulate themselves through thinking, feeling, behaving, acting, being responsible for the decisions made and living them with social considerations. Several existing instruments for assessing student autonomy still contain items that are not yet relevant to the needs of Indonesian students. This presents an interesting opportunity to develop and adapt them to the diverse social, cultural, institutional, and academic backgrounds of Indonesian students, as well as the dynamics of diverse student populations. This study aims to develop a scale to validate student autonomy used purposive sampling. This study was conducted in 2024, involving 378 students as participants consisting of 39 males and 339 females aged 17-23 years at Padang State University. This instrument is called the Student Autonomy Scale. This study uses a quantitative approach with 40 questions with "yes-no" formats as answer choices—data analysis using the Rasch model and Winsteps software. The results showed that the Cronbach Alpha value, which measures the interaction between people and items, was 0.68, included in the sufficient category. In addition, the item reliability of 0.99 indicates that the items in the autonomy questionnaire can be used to measure autonomy in students. The use of theory-based assessment methods, cross-cultural trials, and adaptive technology are some of the solutions proposed to improve the measurement quality. The Student Autonomy Scale developed in this study has a novelty that is specifically designed for the context of students in Indonesia with various considerations by adapting a comprehensive autonomy theory and integrating several important aspects and providing more precise, accurate, and standardized analysis in the era of disruption and the 21st century.